If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-35=5(v-6)
We move all terms to the left:
-35-(5(v-6))=0
We calculate terms in parentheses: -(5(v-6)), so:We get rid of parentheses
5(v-6)
We multiply parentheses
5v-30
Back to the equation:
-(5v-30)
-5v+30-35=0
We add all the numbers together, and all the variables
-5v-5=0
We move all terms containing v to the left, all other terms to the right
-5v=5
v=5/-5
v=-1
| 6+2t=−12 | | -9n-7=-7-9n | | 5w+4=9+4w | | -5b-40=30 | | 9x+21=70+4x+6 | | -10+b=-b | | x/3-5/(x+5)=4 | | f+41=-17 | | 19j-9j=20 | | 3s-8=8s-8 | | x+2x+14=5x2 | | -8(5y-2)=18-7y | | 5t-8=5t | | 6-5(3x-2)=44 | | s+5=s-1 | | 8+10w=9w | | 2(5v+1)=82 | | -7k=k-8 | | 9(5v-2)=19+4v | | 4q+q+3q-8=16 | | -37=a/14 | | 2(x=10)=3x-30 | | 15d-10d+5=15 | | d+-28=-92 | | -9b-7=-10b | | 45=-x+6x-10 | | -29+4f=7(5f+9) | | 13v-2v-9v=20 | | 14x-2=10+12x | | -4z+9z=-20 | | -15n+18n=-18 | | 4(4y+1)=3(2y+4) |